The boy who lost Fairyland - Valente, Catherynne M. 1979- (Feiwel & Friends, 2015)
"A young troll named Hawthorn is stolen from Fairyland by the Golden Wind, and becomes a changeling in our world, a place no less bizarre than Fairyland in his eyes"...
Keywords: JUVENILE FICTION / Fantasy & Magic; Fantasy; Trolls; Changelings; Jugendbuch